Jurisdicional Protection of springs in the combined perspective of water resouces policy and forest code: Contributions, advances and mismatches. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This paper consists of a survey and analysis on a topic of vital importance to life: the springs. Based on the historical evolution of Environmental Law, it is urgent to emphasize that a society that does not preserve its springs is destined to face a serious water crisis, such as that of contemporaneity, which compromises the right to a healthy and balanced environment. In this scenario, the water aspects and their configurations and legal guardianships are analyzed, emphasizing the importance of both small and large water courses, such as rivers, streams and waterfalls. As the objective of this study, special attention was focused on springs and springs, which have significant potential for sustainability and promotion of health and quality of life, as well as sustainable tourism, requiring special protection, in line with the National Policy of Water Resources. An accurate analysis of the definitions of the Forest Code on these environmental assets and specially protected areas linked to these resources was also sought, as a contribution to the creation and planning of public policies for the management and conservation of these natural environments, as a suitable tool for their protection and guardianship. The research is justified given the need to seek effective compliance with the fundamental right of a healthy and balanced environment, reflecting a guaranteed future in terms of quality and conservation of natural resources, in order to explore their potential in a sustainable way. The methodology adopted is exploratory-bibliographic, under constitutional, legislative, jurisprudential and doctrinal hermeneutic analysis.